Poignancy Flavor - Kotov, Nikolay (Taideyliopiston Kuvataideakatemia, 2023)
This text, submitted in fulfillment of the required written component of the MFA thesis, titled 'poignancy flavor,' serves as a collection of fragmented thoughts and experiences, offering a glimpse into the artist’s perspective on life, work, and their own body as inseparable within their existence. By acknowledging personal struggles in writing, Kolya chooses to explore writing itself as an art form and as a part of their art practice. This is a reflection on their life experiences and creative process through the themes of identity, loneliness, and the pursuit of love and connection. It highlights moments of both support and resistance within their family and looks into the challenges of vulnerability in a family marked by generational trauma. The central focus is on Kolya’s art project, 'opus phase iii,' exhibited at KK23 as the practical component of this MFA thesis, which intimately glimpses into their gender affirmation journey. This multidisciplinary work combines experimentation with photography on textiles, automated by programmed motors. In the written component artist acknowledges the role of artificial intelligence as a collaborative tool in the creative process, blurring the lines between human and machine authorship. The written thesis contains an excerpt of a script from a video project, that was intended to be the practical component of this thesis but later discarded. The narrative of the script transports us into the autofictional director's struggles with social anxiety and missed creative opportunities. It paints a vivid picture of his world, filled with faded dreams. The artist looks back at their previous works marked by phases to unfold the evolution and significance of ‘yellow phase i’ and its transformation into 'afflatus phase ii,' which pays homage to a social media influencer by creating elements inspired by the work and body of Michaela Stark. In conclusion, this text reflects on the importance of phases in Kolya’s artistic practice. It highlights their defiance against established norms and their commitment to seamlessly blending life and art. The text also hints at future projects that will continue to push the boundaries of artistic exploration.
Keywords: taiteellinen työ; kuvataide; taidenäyttelyt; installaatiot; tekstiilitaiteilijat; identiteetti; tilataide; tekstiilitaide; fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|